A CMOS/SOI single-input PWM discriminator for low-voltage body-implanted applications - De Lima, J. A.; Silva, S. F.; Cordeiro, A. S.; Verleysen, M. (Taylor & Francis Ltd, 2002)
A CMOS/SOI circuit to decode Pulse-Width Modulation (PWM) signals is presented as part of a body-implanted neurostimulator for visual prosthesis. Since encoded data is the sole input to the circuit, the decoding technique is based on a novel double-integration concept and does not require low-pass filtering. Non-overlapping control phases are internally derived from the incoming pulses and a fast-settling comparator ensures good discrimination accuracy in the megahertz range. The circuit was integrated on a 2 mum single-metal thin-film CMOS/SOI fabrication process and has an effective area of 2 mm(2). Measured resolution of encoding parameter a is better than 10% at 6 MHz and V-DD = 3.3 V. Idle-mode consumption is 340 LW. Pulses of frequencies up to 15 MHz and alpha = 10% can be discriminated for 2.3 V less than or equal to V-DD less than or equal to 3.3 V. Such an excellent immunity to V-DD deviations meets a design specification with respect to inherent coupling losses on transmitting data and power by means of a transcutaneous link.
Keywords: PWM decoder; SOI design; low-voltage comparators; implanted circuits; visual prosthesis